AKULTURASI ISLAM SUNDA (Kajian terhadap Tradisi Hajat Sasih) - Abdurrahman Misno Bambang (IBDA': Jurnal Kebudayaan Islam, 2013)
This research is about Idul Adha festival which is combined with Hajat Sasih, a ritual that is spread out in Kampung Naga. Phenomenological approach with ethno science paradigm by James P. Spradley is used to record the festival. It has been found that the festival is without slaughtering the livestock and the Hajat Sasih ritual is dominated the festival. Hajat Sasih is a kind of thankfulness to God by visiting the cemetery of the ancestors; Sembah Dalem Eyang Singaparana besides it is also a special moment for the people to get the benefit of silaturahmi, ziarah kubur and tumpeng which are blessed by the senior villager. The people are presenting a gift to religious leaders and village leaders.